The Implementation of Criminal against Corporation in Environmental Crime - Andini Wiranti; Nur Azisa; Haeranah Haeranah (LEGAL BRIEF, 2022)
This study aims to identify and analyze the Implementation of criminal aginst corporation in environtmental crime. This research uses empirical legal research methods, which examines the law as a social phenomenon. The random sampling method was used to collect samples from the Department of Environmental Services and the Makassar District Court. Data collection techniques are based on the needs of analysis and evaluation and are carried out in two ways: directly in interviews and through library research. The results of the study indicate that the implementation of punishment against corporations for environmental crimes is carried out if the settlement through administrative and civil sanctions is ineffective, with the goal of providing a different effect on corporations that commit environmental crimes.